Alternative Energy Sources for Energy Crisis: Rethinking the Global and Bangladesh Perspectives - Islam, Md. Shafiqul (Journal of Technology Innovations in Renewable Energy, 2017)
This paper discusses the evolution of various energy resources, their reserves, and usages for policy makers and energy experts. It finds that there is a huge supply-side deficit to meet the demand of the 7 billion people in today's world. To meet this huge energy needs, alternative energy sources are investigated and suggestions are made to address energy crises in Bangladesh and global contexts. The author argues that with the advancement of technology, a completely new nuclear meaning thorium reactors, small modular reactors, and novel solar technologies can offer potential alternatives to meet the needs of mankind. In addition, developing cost-effective carbon capture storage devices to catch carbon at its generating sources, energy storage devices, and energy culture model can be explored. The search for alternative technologies and energy culture require robust discussion, cooperation, and investment in clean energy sources. The paper concludes with a discussion of future energy policy and appropriate action plans to adopt emerging alternative technologies as per the promises made at the Paris Climate Change Accord COP21.